(untitled) (The International Journal for Scientific Research, 2023)
The current study aimed to investigate the level of application of excellence management according to the European model standards from the point of view of female teachers in North Al Batinah Governorate and to enquire significant differences between the averages of female teachers with respect to the standards according to the cycle. To achieve the objectives of the study, the descriptive approach was used. The sample was selected randomly and consisted of (150) female teachers from the schools of the cycle 1 (4-1) and cycle 2 (10-5) in North Al Batinah Governorate. The study tool (questionnaire) consisted of (41) items distributed on six dimensions: (policies and strategies, employee satisfaction (individuals), partnerships and resources, operations, community interaction, school performance results), It was applied to the sample after verifying its psychometric characteristics. Findings showed that the level of application of excellence management according to the European model of excellence from the point of view of female teachers in North Al Batinah Governorate was high, as the results indicated that there were no statistically significant differences at the level of significance (α ≤ 0.05 between the arithmetic means of the level of excellence management application according to the European model from the point of view of the parameters attributed to the episode variable (first/ second), In the light of the results obtained, the researcher recommended the necessity of developing a national model for the management of excellence in the Sultanate, or working on adopting one of the international models for managing excellence; This is to support excellence and its application in all public schools, and to train school administrations on modern systems and trends in school management, to enhance their distinguished skills, and to work on refining the research skills of school principals, to practice scientific research to apply its results in the service of the educational institution, and to activate school administrations for several methods Effective measure of employee satisfaction with the services provided to them by the school Among the recommendations are also the provision of developed programs for property management, and the involvement of local community members in setting the annual school plan, in addition to designing an educational guide to spread the culture of managing excellence in public schools, the initiative of school administrations to form a team for school excellence, which monitors the extent to which excellence practices are applied and strengthened among all employees.